Analisis dan Desain Sistem Informasi Geografis untuk Pemetaan Infrastruktur Pemerintahan (Studi Kasus: Kota Pontianak) - Ramadhani, Dochi; Permana, Ryan; Lesmana, Chandra (Universitas Pendidikan Ganesha, 2018)
The purpose of this research is to produce an application of geographic information system that can help Bappeda Pontianak City and other related parties in: 1) managing information of government infrastructure, 2) mapping the location of government infrastructure deployment, 3) handling historical data of government infrastructure, 4) provides information on the condition of government infrastructure so as to better support infrastructure maintenance planning and local revenue management. This research is done by storing the data attribute infrastructure into a tabular data, then mapping infrastructure based on the location where the infrastructure is built into a thematic layer. The thematic layers are then arranged overlaid with other layers and relate to tabular data so that it can be analyzed based on geographic conditions (spatial analysis) as well as analysis based on tabular data and client-server function so that the number of infrastructure points on the admin and user side amounts to same. The resulting system can handle the data input process and data search process and perform spatial functions well. The data input by the user is always validated and there is feedback to the user when an error occurs. The system is capable of handling historical data of an infrastructure based on the infrastructure point id and displaying it in the form of attribute data. The system can show the deployment of infrastructure in Pontianak City which is described in the form of maps so that users can know more clearly the location and condition of existing infrastructure. The results of research using blackbox testing by looking directly the results of existing applications.